Integrating TPACK and digcompedu to strengthen primary school teachers’ digital competence - Dwinita, Gina Garnika; Heri, Asep; Iskandar, Sofyan (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
The rapid digitalisation of education requires teachers to develop comprehensive competence that integrates technological, pedagogical, and ethical digital practices. However, existing research often examines the Technological Pedagogical and Content Knowledge (TPACK) model and the Digital Competence of Educators (DigCompEdu) framework separately, resulting in limited conceptual guidance on how both can be systematically combined to strengthen teachers’ digital competence. This study applies a qualitative systematic literature review using the PRISMA 2020 protocol to analyse peer-reviewed articles published between 2017 and 2025 across Scopus, ERIC, and SINTA databases. Thirty studies met the inclusion criteria and were synthesised thematically. The findings show that TPACK provides the pedagogical–technological knowledge base, while DigCompEdu operationalises digital professionalism through measurable and ethical indicators. Their integration promotes reflective, inclusive, and learner-centred digital pedagogy and offers a multi-level foundation aligned with global policies (SDG 4), national education reforms (Merdeka Belajar), and institutional digital ecosystems. This review proposes an integrated conceptual map highlighting how global, national, institutional, and teacher-level factors interact to support digital competence development. The integrated framework provides direction for professional development, curriculum design, and future empirical validation in primary education.